Description of Chlorogomphus danhkyi sp. nov. from Vu Quang National Park, central Vietnam with notes on other congeners from the Park (Odonata: Chlorogomphidae) - Phan, Quoc Toan; Karube, Haruki; Hung, Nguyen Viet; Anh, Tran Dinh (Zootaxa, 2021)
Chlorogomphus danhkyi sp. nov. (Holotype ♂: Khe Ro, Vu Quang National Park, Ha Tinh Province, 15.0444 N, 107.9270 E, altitude 1480 m) based on both sexes is described. The new species differs from Chlorogomphus piaoacensis Karube, 2013 mainly by the shape of male cerci. Other species of Chlorogomphus Selys, 1854 from Vu Quang National Park are also recorded.